Disseminated Tuberculosis Presenting as Chronic Orchiepididymitis in a Military Trainee: A Case Report and Review of the Literature - Michael U. Williams; Ashley Burris; Amy Zingalis; David A. Lindholm; Brian K. White (Case Reports in Infectious Diseases)
Orchiepididymitis is a clinical diagnosis. The acute form secondary to sexually transmitted or enteric pathogens is well known to primary care providers. However, chronic orchiepididymitis may be secondary to genitourinary tuberculosis (TB), and physicians in countries with a low prevalence of TB might not consider it in their differential diagnosis. Indeed, cognitive errors, such as anchoring or availability bias, may contribute to a delayed diagnosis of genitourinary TB. We present a case of chronic orchiepididymitis as a result of disseminated TB in a Cameroonian male who was visiting the United States for military training. He experienced diagnostic delay and was ultimately diagnosed by orchiectomy. Early consideration of a diagnosis of TB for chronic or recurrent orchiepididymitis in a patient with epidemiologic risk factors is of utmost importance because delayed diagnosis could lead to organ loss.